Recombinant SADS-CoV as a vector for porcine epidemic diarrhea vaccine development - Yan, Xiaoling; Zhang, Xiaoli; Lyu, Xiaocheng; Zheng, Yaoyao; Li, Qianniu; Zhao, Xiaoya; Fu, Jun; Ma, Jingyun (Frontiers in Immunology, 2025)
IntroductionSwine acute diarrhea syndrome coronavirus (SADS-CoV) is an emerging porcine enteric coronavirus that can cause diarrhea in piglets younger than 5 days of age. However, infection of pigs older than 5 days of age does not usually result in obvious clinical symptoms. This relative intrinsic safety in older animals prompted us to investigate the potential of SADS-CoV as a viral vector for porcine diarrhea virus vaccines.MethodsWe utilized Gibson assembly to clone the SADS-CoV sequence into an artificial bacterial chromosome (BAC) vector. Further manipulation was carried out by recombineering to generate four attenuated recombinant SADS-CoV strains expressing a PEDV protective antigen fused with peptides that target immune cells. Subsequently, the biological characteristics and immunogenic efficacy of these four recombinant strains were systematically assessed through in vitro cell models and in vivo animal challenge experiments.Results and discussionThe recombinant viruses exhibited a proliferation profile similar to that of the wild-type virus in Vero cells, maintained stable cytopathic effects, retained the exogenous sequences for up to 20 passages, and consistently expressed the PEDV antigen fusion protein. Immunizing pregnant sows with these recombinant viruses effectively enhanced both cellular and mucosal immune responses and provided significant clinical protection against PEDV to their offspring. This study not only generated a vaccine candidate for PEDV but also established a pipeline for using the SADS-CoV as a vector for vaccine development.